2000
DOI: 10.1101/gr.10.12.2030
|View full text |Cite
|
Sign up to set email alerts
|

Gene Discovery Using Computational and Microarray Analysis of Transcription in the Drosophila melanogaster Testis

Abstract: Identification and annotation of all the genes in the sequenced Drosophila genome is a work in progress. Wild-type testis function requires many genes and is thus of potentially high value for the identification of transcription units. We therefore undertook a survey of the repertoire of genes expressed in the Drosophila testis by computational and microarray analysis. We generated 3141 high-quality testis expressed sequence tags (ESTs). Testis ESTs computationally collapsed into 1560 cDNA set used for further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
132
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(139 citation statements)
references
References 44 publications
7
132
0
Order By: Relevance
“…1A). Recent work has shown that sex-biased gene expression is significant in Drosophila (6)(7)(8). This first report of sex-biased expression of the full (predicted) genome also strongly indicates that there is significant sex-biased expression-especially in gonads (Fig.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…1A). Recent work has shown that sex-biased gene expression is significant in Drosophila (6)(7)(8). This first report of sex-biased expression of the full (predicted) genome also strongly indicates that there is significant sex-biased expression-especially in gonads (Fig.…”
mentioning
confidence: 87%
“…Testis and male-specific accessory gland ESTs are biased toward autosomal locations (8,9), which suggests that the X chromosome is not a favored location for genes differentially expressed in the male soma. In contrast, the chromosomal distribution of ovary ESTs from the Berkeley Drosophila Genome Project (10) was random.…”
mentioning
confidence: 99%
“…These genes, annotated according to their presence in various EST libraries (see materials and methods), can be used to test the extent and details of molecular sexual dimorphism in expression (Andrews et al 2000;Parisi et al 2004) as well as the evolution of reproductive (testis and ovary) genes relative to presumably nonreproductive (head) genes (Coulthart and Singh 1988;Civetta and Singh 1995;Jagadeeshan and Singh 2005). Previous studies, which have used a limited number of genes, have suggested that the testis transcriptome may have a greater proportion of rapidly evolving genes relative to ovary or head (Civetta and Singh 1995;Jagadeeshan and Singh 2005) and that rates of evolution of testis-expressed genes are far higher than rapidly evolving genes expressed in ovary and head.…”
mentioning
confidence: 99%
“…Increasing importance has also been attributed to ESTs as a tool for the annotation of complete genome sequences of mammalians and plants. Unique ESTs provided biological evidence of hundreds of predicted genes, newly discovered genes, or transcript isoforms leading to considerable advance in gene identification mission in multicellular organisms (Andrews et al, 2000). Today, more than ten million ESTs are currently available through the dbEST entry of GenBank (http://www.ncbi.nlm.nih.gov/dbEST/dbEST_sumary.htm l); however, only 14% of dbEST release 022301 of February 23, 2001 corresponds to plant sequences.…”
Section: Introductionmentioning
confidence: 99%